MACROECONOMIC ANALYSIS OF THE SECURITIES MARKET OF THE REPUBLIC OF ARMENIA - Niyazbekova Shakizada; Grekov Igor; Blokhina Tatyana; Mussirov Galym; Aetdinova Rasulya; Suleimenova B.B.; Konstantin Bunevich; Burkaltseva Diana (Scientific Journal of Pedagogy and Economics, 2020)
The article deals with the problems of the development of the securities market of the Republic of Armenia. The main changes that have occurred in recent years in the securities market in the Republic of Armenia have been investigated. Methods for analyzing the securities market of the Republic of Armenia are proposed. The indicators of the securities market are considered and the main trends of its development are revealed. This article presents the structure of the securities market of the Republic of Armenia in terms of trading volume. We chose the macroeconomic analysis as a method of our research, as it constitutes an integral element for the fundamental analysis of the securities market. With the help of the macroeconomic analysis an investor effects vigilance and analyses of the basic economic indicators; thus he also defines the extent of their influence on the securities market dynamic. It is the macroeconomic analysis that provides investors with the possibility to define which element of the financial market (securities, currency, credit) is currently the most profitable and attractive for to invest into.